2020
DOI: 10.3389/fnmol.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids as Selective Inhibitors of Glycine Receptor Activity: Structure-Activity Relationship Study on Endogenous Androstanes and Androstenes

Abstract: The ability of androstane and androstene neurosteroids with modifications at C-17, C-5, and C-3 (compounds 1-9) to influence the functional activity of inhibitory glycine and γ-aminobutyric acid (GABA) receptors was estimated. The glycine-and GABAinduced chloride current (I Gly and I GABA) were measured in isolated pyramidal neurons of the rat hippocampus and isolated rat cerebellar Purkinje cells, correspondingly, using the patch-clamp technique. Our results demonstrate that all the nine neurosteroids display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…It can be assumed that some of these sites are responsible for desensitization and can interact with each other. The results of this work generally coincide with our previous results obtained on the same model with other steroids: pregnanes, androstanes, and androstenes . With those steroids, we reported the same tendency, i.e., higher potency of the substances to accelerate desensitization than to reduce the peak amplitude of I Gly .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It can be assumed that some of these sites are responsible for desensitization and can interact with each other. The results of this work generally coincide with our previous results obtained on the same model with other steroids: pregnanes, androstanes, and androstenes . With those steroids, we reported the same tendency, i.e., higher potency of the substances to accelerate desensitization than to reduce the peak amplitude of I Gly .…”
Section: Discussionsupporting
confidence: 91%
“…The effects of NSs with pregnane and androstane structure on glycine-induced chloride current ( I Gly ) were studied on a culture of rat spinal neurons and on recombinant GlyRs expressed in Xenopus oocytes. , Our recent studies described the effect of NSs on I Gly in isolated rat hippocampal pyramidal neurons. Using this model, we have shown that NSs with pregnane, androstane, and androstene structures decrease I Gly by accelerating desensitization and reducing peak amplitude. The effects of corticosteroids on I Gly have not yet been investigated. In the present work, we studied the effect of ten corticosteroids and their derivatives on I Gly in isolated rat hippocampal pyramidal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our structure-activity relationship study will serve as a useful platform for understanding the mechanisms of physiological effects of pregnane NSs. Moreover, together with our previously published descriptive study of NSs with androstane skeleton (J. V. Bukanova et al, 2020) and the scheduled study on corticosteroids will afford comprehensive overview of the influence of endogenous steroids and NSs on the I GABA and I Gly . Rat pups were kept with their mother in separate cage with permanent access to manufactured complete feedstuff and water.…”
Section: Introductionmentioning
confidence: 95%
“…In the CNS, the best-known receptors modulated by NAS are type A γ-aminobutyric acid (GABA A ) receptors and glutamate receptors including NMDA receptors, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and kainate receptors ( Joëls, 1997 ; Wu and Chen, 1997 ; Wu et al, 1998 ; Yaghoubi et al, 1998 ; Beyenburg et al, 2001 ; Rupprecht, 2003 ; Shirakawa et al, 2005 ). Furthermore, interactions of NAS with glycine, transient receptor potential (TRP), nicotinic acetylcholine, muscarinic acetylcholine, sigma (σ)-receptors and several types of voltage-gated calcium channel were reported ( Klangkalya and Chan, 1988 ; Valera et al, 1992 ; Monnet et al, 1995 ; Hu et al, 2007 ; Xu et al, 2008 ; Majeed et al, 2012 ; Bukanova et al, 2020 ).…”
Section: Mechanism Of Action Of Neuroactive Steroidsmentioning
confidence: 99%